Angioma serpiginosum: a case report and review of the literature - Andrea Diociaiuti; Mario Cutrone; Roberta Rotunno; Rita De Vito; Iria Neri; Elisa Pisaneschi; May El Hachem (BMC, 2019)
Abstract Background Angioma serpiginosum is a rare vascular anomaly whose pathogenesis is still unknown. It is characterized by the onset of vascular reddish macules and papules during childhood, lesions are usually monolateral with a linear serpiginous pattern. It is rarely associated with extracutaneous findings. This entity has not yet been included in the classification of the International Society for the Study of Vascular Anomalies. Case presentation We describe the first Italian report of angioma serpiginosum with a congenital symmetrical presentation. The patient had a further extension of macules during puberty involving both of the soles. No extracutaneous manifestations were present. Diagnosis was confirmed with dermoscopy and light microscopy that revealed the typical clusters of dilated, thickened and PAS+ capillaries in the upper dermis. Moreover, Immunohistochemistry showed positive WT-1 staining. Genetic analysis with next generation sequencing did not detected any mutation. Conclusions Our patient presented a peculiar symmetrical and planar extension with a serpiginous linear pattern. The proliferative nature of this condition has been widely discussed in literature. In our case immunohistochemistry was positive for Wilms tumor-1, a new endothelial marker expressed during angiogenesis in reparative processes and endothelial tumors. Clinical evolution, histological and immunohistochemical findings suggest that angioma serpiginosum should be considered as a vascular proliferation. For these reasons we think it should be included in the international classification as a tumor.